2022
DOI: 10.1186/s40364-022-00394-0
|View full text |Cite
|
Sign up to set email alerts
|

IGSF11 and VISTA: a pair of promising immune checkpoints in tumor immunotherapy

Abstract: Immunotherapy has become the major treatment for tumors in clinical practice, but some intractable problems such as the low response rate and high rates of immune-related adverse events still hinder the progress of tumor immunotherapy. Hence, it is essential to explore additional immunotherapy treatment targets. In this review, we focus on the structure, expression and expression-related mechanisms, interactions, biological functions and the progress in preclinical/clinical research of IGSF11 and VISTA in tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…reported that increased expression of VSIG-3 in glioma tissue is associated with high infiltration of immune cells (especially CD4 + and CD8 + T cells), in addition, the expression of IL-10 and TGF-β increases with increased VISTA expression [42] . Xi Yang Tang et al have speculated that VISTA may interact with IGSF11 for immune regulation in other tumors, including non-small cell lung cancer, ovarian cancer, gastric cancer, colorectal cancer, soft tissue sarcoma, and oral squamous cell carcinoma [48] . The Vista-targeting antibody HMBD-002 can effectively block the interaction between VISTA and IGSF11, further inhibiting IGSF11-mediated T cell production of IFN-γ [49] .…”
Section: Discussionmentioning
confidence: 99%
“…reported that increased expression of VSIG-3 in glioma tissue is associated with high infiltration of immune cells (especially CD4 + and CD8 + T cells), in addition, the expression of IL-10 and TGF-β increases with increased VISTA expression [42] . Xi Yang Tang et al have speculated that VISTA may interact with IGSF11 for immune regulation in other tumors, including non-small cell lung cancer, ovarian cancer, gastric cancer, colorectal cancer, soft tissue sarcoma, and oral squamous cell carcinoma [48] . The Vista-targeting antibody HMBD-002 can effectively block the interaction between VISTA and IGSF11, further inhibiting IGSF11-mediated T cell production of IFN-γ [49] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, in breast cancer, VISTA expression was associated with a better prognosis in triple-negative patients [29,30]. In other types of tumors, such as gliomas, endometrial cancer, prostate cancer, and mesothelioma, the expression varies after treatment; however, in most of these cases, positivity and high expression are related to an advanced stage and poor outcome [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, VISTA offers another compensatory inhibitory pathway in prostate tumors after anti-CTLA-4 therapy ( 34 ). In summary, VISTA is considered a potential therapeutic target for anticancer therapy that plays a vital role in immunosuppression ( 35 ). However, little is known about VISTA expression and its relevant mechanisms in MM.…”
Section: Introductionmentioning
confidence: 99%